Development Of L2TP IPSec for Enhancing Private Network Scalability: Performance, Cost, and Regulatory Framework - Mochammad Iqbal Fahriza; Rendy Munadi; Helni Mutiarsih Jumhur (CV. Syntax Corporation Indonesia, 2025)
This research explores the implementation of L2TP IPSec private networks as a secure and cost-effective solution for data transmission in corporate environments. The primary objective is to address the challenges of ensuring secure data transfer over private networks while meeting technical, economic, and regulatory requirements, particularly within the context of Indonesia. The research employs a comprehensive methodology that includes network topology design and simulation using Cisco Packet Tracer, an economic feasibility analysis incorporating CAPEX, OPEX, NPV, IRR, PI, and PP metrics, and a regulatory review based on Indonesia’s Electronic Information and Trans- action Law (UU ITE). By examining the integration of L2TP and IPSec protocols, this study evaluates their effectiveness in safe- guarding sensitive corporate data when transmitted over public networks. The hypotheses focus on enhanced transmission data, cost, and regulatory compliance. The findings provide insights into the technical performance, economic viability, and legal alignment of L2TP IPSec private networks in Indonesia. This research offers a robust framework for enterprises to develop secure, scalable, and compliant private network infrastructures. Keywords: Private Network, L2TP, IPSec